2020
DOI: 10.1038/s41598-020-67883-w
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Epstein–Barr virus infection in multiple sclerosis development

Abstract: It is unclear whether smoking interacts with different aspects of Epstein-Barr virus (EBV) infection with regard to multiple sclerosis (MS) risk. We aimed to investigate whether smoking acts synergistically with elevated EBNA-1 antibody levels or infectious mononucleosis (IM) history regarding MS risk. Two Swedish population-based case-control studies were used (6,340 cases and 6,219 matched controls). Subjects with different smoking, EBNA-1 and IM status were compared regarding MS risk, by calculating odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…After stratification by other predisposing factors for MS like HLA DRB1*15:01, vitamin D deficiency and smoking habit, EBNA-1 and VCA IgG prevalences and titers remained significantly higher in MS patients than in controls. A recent study with the Swedish cohort showed that smokers had higher EBNA-1 antibody levels than never smokers; authors suggested that smoking habit and EBNA-1 antibody levels could act synergistically to increase MS risk ( 16 ). Interestingly, we did not find a significant difference in EBNA-1 and VCA IgG prevalences between current smokers (MS patients and controls); a higher prevalence of both antibodies was found in the control group of current smokers than in the control group of no smokers, although this increase was not higher enough to be significantly different between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…After stratification by other predisposing factors for MS like HLA DRB1*15:01, vitamin D deficiency and smoking habit, EBNA-1 and VCA IgG prevalences and titers remained significantly higher in MS patients than in controls. A recent study with the Swedish cohort showed that smokers had higher EBNA-1 antibody levels than never smokers; authors suggested that smoking habit and EBNA-1 antibody levels could act synergistically to increase MS risk ( 16 ). Interestingly, we did not find a significant difference in EBNA-1 and VCA IgG prevalences between current smokers (MS patients and controls); a higher prevalence of both antibodies was found in the control group of current smokers than in the control group of no smokers, although this increase was not higher enough to be significantly different between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cigarettes is a well‐established risk factor for MS. 152 Recently, the impact of smoking on EBV reactivation and circulating levels of anti‐EBNA IgG and IgA has been investigated. 153 These and other studies 154 suggest that smoking may promote EBV reactivation and increase serum EBNA‐1 IgG antibody levels. Furthermore, a history of IM and smoking appears to interact to increase the risk of MS. 153 Cigarette smoking also affects the composition of the gut microbiome 155 and may interact with other factors affecting the gut microbiome in MS patients.…”
Section: Potential Effects Of Changes In Gut Microbiome Low Sun Expos...mentioning
confidence: 83%
“… 153 These and other studies 154 suggest that smoking may promote EBV reactivation and increase serum EBNA‐1 IgG antibody levels. Furthermore, a history of IM and smoking appears to interact to increase the risk of MS. 153 Cigarette smoking also affects the composition of the gut microbiome 155 and may interact with other factors affecting the gut microbiome in MS patients. Smoking induces an expansion of circulating cMBCs, including IgA + cells, 156 , 157 but this effect may be transient because circulating B‐cell profiles are not different in smokers and non‐smokers.…”
Section: Potential Effects Of Changes In Gut Microbiome Low Sun Expos...mentioning
confidence: 83%
“…EBV infection can induce organismal immune disorders and promote the development of MS ( Hedstrom et al, 2020 ). The majority of adult patients with MS are EBV-positive before the onset of MS, indicating that EBV-seronegative individuals have a low risk of MS ( Drosu et al, 2021 ).…”
Section: Ebv and Multiple Sclerosismentioning
confidence: 99%